EFFECTIVE MECHANISMS OF REGULATING TAXATION FOR THE USE OF WATER RESOURCES IN THE CONDITIONS OF WATER STERILITY IN UZBEKISTAN (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This scientific article is devoted to the analysis of effective mechanisms for taxation of water resources in Uzbekistan in conditions of water scarcity. In Central Asia, and in particular in Uzbekistan, water resource scarcity is becoming an increasingly urgent problem due to factors such as economic growth, population growth, and climate change.